Perkembangan Pranata Pertanahan dalam Pengembangan Kota Baru Padang - Diana Rahayu Evelina; Lita Sari Barus (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
After the earthquake that hit Padang City in 2009, the city development has been changed its direction. The city development which previously centered on the coast has turn to the east of the city, which was an agriculture area. Development of Eastern Area carry out a fairly large function as the central government area and residential development area. The emergence of The New City of Padang development policy is expected to become a policy in city management as a mandate from National Medium-Term Development Plan (RPJMN). The problem in developing this function is the lands in this area are customary lands/land controlled by the tribes in the eastern region of Padang. Therefore, it is necessary to know how the development of land regulation in Padang City in the management of the city. According to Tjuk Kuswartojo’s Human Habitat Development, land regulations in Padang City can be described in responding to the challenges of developing new cities in this region. The land institutions in Padang City is heavily influenced by customary system, therefore collaboration between the local government and customary authorities in Padang City is needed to create a new city.